Three ethical frames of reference: insights into Millennials' ethical judgements and intentions in the workplace. (23rd July 2015) - Culiberg, Barbara; Mihelič, Katarina Katja
Abstract : The paper investigates the ethical decisions of Millennials, who are not only part of an expanding cohort of the workforce, but also represent potential future managers with a growing influence on work practices and employment relationships. In the conceptual model, we propose that three ethical frames of reference, represented by perceived organisational ethics, perceived employee ethics and reflective moral attentiveness, antecede ethical judgements, which further influence the ethical intentions of Millennials. Using structural equation modelling, we test the model for three different business ethics scenarios: paying a consulting fee, dumping hazardous waste, and running an offensive advertising campaign. The findings confirm the link between ethical judgements and intentions across the board, while the influence of the ethical frames of reference varies among the scenarios. We propose that the differences in the predictive ability of the ethical frames of reference depend on the nature of the ethical issue, which holds important implications for today's managers in their attempts to encourage ethical behaviour of Millennial employees.